IMPLEMENTATION OF DEBT TO EQUITY SWAP AS A STEP FOR COMPANIES IN FACING THE THREAT OF BANKRUPTCY - Najla Rafiki; Rianda Dirkareshza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This article examines the implementation of debt to equity swap as a strategic legal mechanism for companies facing the threat of bankruptcy within the Indonesian legal system. The study departs from the phenomenon of corporate over-leverage and the increasing use of Postponement of Debt Payment Obligations (PKPU) as a forum for debt restructuring, and focuses on how the conversion of debt into shares can operate as an alternative corporate rescue tool rather than a purely financial technique. Using a normative legal research method with a statute, case, and conceptual approach, the research analyzes the legal framework governing debt to equity swap, including bankruptcy law, company law, and capital market regulation, and is conceptually grounded in Lawrence M. Friedman's legal system theory, encompassing legal structure, substance, and culture. The discussion is supported by case studies of PT Garuda Indonesia, PT Darma Henwa Tbk, and PT Bakrie & Brothers Tbk to assess the practical application, procedural requirements, and consequences of debt to equity swap. The findings indicate that, under appropriate conditions, debt to equity swaps can mitigate bankruptcy risk, restore financial health, recalibrate the relationship between companies and creditors, and strengthen ongoing concerns while still requiring careful attention to shareholder protection and regulatory compliance.